Number and brightness analysis of sFRP4 domains in live cells demonstrates vesicle association signal of the NLD domain and dynamic intracellular responses to Wnt3a. (July 2015) - Perumal, Vanathi; Krishnan, Kannan; Gratton, Enrico; Dharmarajan, Arun M.; Fox, Simon A.
Abstract: The Wnts are secreted, lipidated glycoproteins that play a role in cellular processes of differentiation, proliferation, migration, survival, polarity and stem cell self-renewal. The majority of Wnts biological effects are through binding to specific frizzled (Fzd) receptor complexes leading to activation of downstream pathways. Secreted frizzled-related proteins (sFRPs) were first identified as antagonists of Wnt signalling by binding directly to Wnts. They comprise two domains, a Fzd-like cysteine rich domain (CRD) and a netrin-like domain (NLD). Subsequently sFRPs have been shown to also interact with Fzd receptors and more diverse functions have been identified, including potentiation of Wnt signalling. Many aspects of the biology of this family remain to be elucidated. We used the number and brightness ( N & B ) method, a technique based on fluorescence fluctuation analysis, to characterise the intracellular aggregation and trafficking of sFRP4 domains. We expressed sFRP4 and its' domains as EGFP fusions and then characterised the effect of endogenous Wnt3a by fluorescence confocal imaging. We observed vesicular trafficking of sFRP4 and that the NLD domain has a vesicular association signal. We found that sFRP4 and the CRD formed oligomeric aggregates in the perinuclear region while the NLD was distributed evenly throughout the cell with a larger proportion of aggregates. Most significantly we observed intracellular redistribution of sFRP4 in response to Wnt3a suggesting that Wnt3a can modulate intracellular localisation and secretion of sFRP4. Our results reveal a number of novel findings regarding sFRP4 which are likely to have relevance to this wider family.